Influence of forest structure and environmental variables on recruit survival and performance of two Mediterranean tree species (Quercus faginea L. and Q. suber Lam.) - Maltez-Mouro, Sara; García, Luis V.; Freitas, Helena (European Journal of Forest Research, 2008)
We investigated the regeneration requirements of the two dominant tree species in a mixed-oak forest of SW Portugal: Quercus suber (cork oak, evergreen) and Q. faginea (Portuguese oak, winter-deciduous). We hypothesized that (1) recruits of diVerent oak species are diVerentially inXuenced by soil and overstory variables and (2) diVerent factors explain the recruitment occurrence and performance of the same species. We sampled the recruits’ height and diameter, and several environmental and forest structure variables of their microsites. Both recruitment occurrence and performance were modeled using generalized linear models. Our Wnal models predicted the probability of occurrence of recruits of Q. faginea and Q. suber with 74 and 82% of accuracy, respectively, and explained about 50% of the variance of their recruitment performance. The recruits of Q. faginea tended to occur in microsites with higher canopy height, canopy density and litter cover, and closer to both conspeciWc and heterospeciWc adults, while the opposite was true for recruits of Q. suber. The performance of recruits of Q. suber was favored by the higher litter cover (a good surrogate for N and P availability), but negatively aVected by the higher litter depth. We concluded the following: (1) there were signiWcantly diVerent regeneration niches for each species (Q. faginea and Q. suber); (2) the factors explaining the recruitment occurrence diVered from those explaining the recruitment performance; (3) the overstory plays a complex and important role in the regeneration process; (4) diVerent variables apparently related with the same environmental factor (e.g. litter cover and litter depth) could aVect recruits in an opposite way; (5) sensitive trade-oVs must be considered for delineating management actions, since they could favor the regeneration of Q. suber, but, at the same time, negatively aVect the regeneration of Q. faginea.
Keywords: evergreen oak; litter e v ects; litter effects; mediterranean forest; Recruitment; winter-deciduous oak

Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V.; García, A.; Perea, J.; Mata, C.; Gómez, A. G. (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus

ASPECTOS METODOLÓGICOS DE LA ORDENACIÓN DE ENCINARES EN SIERRA MORENA OCCIDENTAL - DOMINGO, J. M.; MARÍN, F. J. (III Congreso Forestal Español, 2001)
This paper presents the analysis of three Management Projects made up for Mediterranean Forest Management Units, mainly composed by evergreen oaks (Quercus ilex ssp. rotundifolia) stands with a low tree density, which are called dehesas. The dehesa is mainly used as range land and normally presents hilly landforms, acidic soils non suitable for agriculture, a temperate-warm climate, and trees covering at least 10% of the surface. It is a man made system which needs work in order to maintain its balance, but it is also a traditional landscape giving highly valued productions. Therefore we must try to find management solutions to preserve an enhance the dehesa systems; one of the greatest problems, tree preservation and renewal is presented here.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español pub-location: Granada
Keywords: Dehesa; evergreen oak; Mediterranean forest management

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA - Esparrago, F.; Vázquez, F. M.; Burzaco, A.; Perez, M. C. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: acorn; Econorny; evergreen oak; feeding; iberian pig; production; Quercus